Three Selected Edible Crops of the Genus Momordica as Potential Sources of Phytochemicals: Biochemical, Nutritional, and Medicinal Values - Muronga, Mashudu; Quispe, Cristina; Tshikhudo, Phumudzo P.; Msagati, Titus A. M; Mudau, Fhatuwani N.; Martorell, Miquel; Salehi, Bahare; Abdull Razis, Ahmad Faizal; Sunusi, Usman; Kamal, Ramla Muhammad; Sharifi-Rad, Javad (Frontiers in Pharmacology, 2021)
Momordica species (Family Cucurbitaceae) are cultivated throughout the world for their edible fruits, leaves, shoots and seeds. Among the species of the genus Momordica, there are three selected species that are used as vegetable, and for medicinal purposes, Momordica charantia L (Bitter melon), Momordica foetida Schumach (Bitter cucumber) and Momordica balsamina L (African pumpkin). The fruits and leaves of these Momordica species are rich in primary and secondary metabolites such as proteins, fibers, minerals (calcium, iron, magnesium, zinc), β-carotene, foliate, ascorbic acid, among others. The extracts from Momordica species are used for the treatment of a variety of diseases and ailments in traditional medicine. Momordica species extracts are reputed to possess anti-diabetic, anti-microbial, anthelmintic bioactivity, abortifacient, anti-bacterial, anti-viral, and play chemo-preventive functions. In this review we summarize the biochemical, nutritional, and medicinal values of three Momordica species (M. charantia, M. foetida and M. balsamina) as promising and innovative sources of natural bioactive compounds for future pharmaceutical usage.